O elo entre o serviço social e o judiciário: demandas, desafios e contribuições na defesa de Direitos - Farias, Meirice Fernandes de (2011)
Unveiling the link between the Social Services and the Judiciary is the object of this work, since the judiciary is constituted as one of the socio-occupational areas of the profession in the sphere of the state, seize the demands placed on professionals which work becomes relevant , considering that these are embody the multiple expressions of social issues, constituting a challenge to social work, while influencing the contributions that the profession has engendered in the defense and expansion rights. It constitutes an analysis from the standpoint of theoretical and methodological basis Qualiquantitative taking for granted the rights violations against children and adolescents in their social, legal and historical guide to the topic. For this we used a theoretical Marxist Behring (2009), Colman (2008), Faleiros (2205), Faria (1999, 2001), Fávaro (2007, 2008), Iamamoto (1985, 1992, 2002, 2006, 2007) Yazbek, Marx (1983), Netto (1994), Nicholas (1984), Pequeno (2009), Rizinni (1997, 2008), Santos (2009), Sales (2006), Telles (1999), Tonet (2009), among others. Besides literature, empirical research conducted through semi-structured interviews using a script and written records and systematic observation / free during interviews. The subjects were 06 social workers from the area of the judiciary to act on Justice for Children and Youth, Family Court and NOADE in Natal / RN. The research aims to analyze the demands and challenges of Social Services and their contribution in ensuring and enforcing rights in courts nowadays. The route established between knowledge and method involves conceptual analysis on the Judiciary, Social Services, and Child and Adolescent Rights. Seize-up in this study the existing contradictions in confronting the multiple expressions of social issues in the context of the judiciary. The research allowed us to identify relevant aspects regarding the challenges and demands placed Social Service; limits on defense and expansion of their rights and contradictions within sociojurídico. For being one of the judiciary institutions that comprise the system warranty rights, social workers also face difficulties in implementing the professional doing since the ills posed by current sociability capital focus in everyday spaces socio-occupational presented here. On the other hand, is commendable acting those protagonists who believe, defend and contribute to the defense and expansion rights